Boosting the Frontier: Australian Settler Colonialism in the Pacific 1860s–1900s. Issue 3 (3rd July 2022) - Halter, Nicholas; Quanchi, Max
Abstract : Australia, itself a union of settler colonies, also gave birth to speculative land and settlement schemes for colonists to migrate to the nearby Pacific Islands and become sugar or copra planters, throughout the period from the 1860s to the early 1900s. The number that migrated to these proposed settler colonies was small, notwithstanding the boosting, promotional rhetoric that accompanied the schemes. Two of these schemes, in the late 1860s and the early 1900s, bookend the era of sub-empire propaganda and imperial jousting that saw hundreds of Australian settlers sail to Fiji and Vanuatu. Both were 'company' schemes, speculative ventures, born out of the nineteenth-century capitalist fervour characteristic of Melbourne and Sydney. A comparison of the two ventures and the boosting literature that supported them reveals the ambiguous promises that were made to settlers and the local challenges that were overlooked in the popular Australian imagination of the region.